Hank the Cowdog: The Frozen Rodeo - Book 74 - Erickson, John R. 1943-; Holmes, Gerald L. (Perryton, TX : Maverick Books, Inc., 2020)
"It's early January on Hank's ranch when Slim and Loper receive word that an ice storm is headed their way. However, just as they're about to prepare the cattle and stock tanks at the ranch to safely weather the storm, Deputy Kile calls with some bad news. It seems that one of their electric fences has short-circuited, and some of their wheat pasture steers have strayed into town and onto the Twitchell golf course! Slim saddles up his horse and heads off to retrieve the steer--with Hank's help of course--but a few mishaps delay his cowboying just long enough to coat Twitchell in ice and turn his steer-roping adventure into a rip-roaring frozen rodeo!"--Publisher's description.
Keywords: Hank the Cowdog (Fictitious character) -- Juvenile fiction; Dogs -- Juvenile fiction; Cowboys -- Juvenile fiction; Rodeos -- Juvenile fiction; Ice storms -- Juvenile fiction; Ranch life -- Juvenile fiction -- West (U.S.); Hank the Cowdog (Fictitious character) -- Fiction; Dogs -- Fiction; Cowboys -- Fiction; Rodeos -- Fiction; Ice storms -- Fiction; Ranch life -- Fiction -- West (U.S.); Humorous fiction; Western fiction